2014
DOI: 10.1021/ef501230c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Compound Classes on the Formation of Sediments in Fossil Fuels During Aging

Abstract: The formation of sediments is a serious instability problem in the storage of fossil fuels. Reactions that lead to sediment formation can be linked to the oxidation of certain fuel components that contain oxygen, nitrogen, or sulfur. To study the oxidation reactions that occur during aging of fuels, we doped a model fuel with several representatives of such compound types. The compounds used were 2,6-dimethylphenol, 2-naphthol, 2,5-dimethylpyrrole, 2-methylindole, dibenzothiophene, and pentamethylene sulfide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…However, before the removal of SCCs, NCCs present in fuels should be eliminated since they reduce the activity of HDS catalysts and hinder the catalytic process itself . Indole (IND) and quinoline (QUI), and their derivatives are the most common NCCs that exist naturally in fossil fuels . NCCs can be classified into two groups: basic and neutral or nonbasic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before the removal of SCCs, NCCs present in fuels should be eliminated since they reduce the activity of HDS catalysts and hinder the catalytic process itself . Indole (IND) and quinoline (QUI), and their derivatives are the most common NCCs that exist naturally in fossil fuels . NCCs can be classified into two groups: basic and neutral or nonbasic.…”
Section: Introductionmentioning
confidence: 99%
“…12 Indole (IND) and quinoline (QUI), and their derivatives are the most common NCCs that exist naturally in fossil fuels. 13 NCCs can be classified into two groups: basic and neutral or nonbasic. IND and its derivatives are neutral, whereas QUIs are basic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…11 NCCs in fuels promote corrosion, 12 adversely affect fuel thermal and storage stability 13−16 and contribute to sediment and gum formation. 17,18 Sediments and gums are major concerns for fuel systems as they plug fuel and engine filters and burner nozzles, which hinders or obstructs fuel flow thereby attenuating engine performance. 19 Past studies evaluated how different classes of NCCs influence the propensity to contribute to stability-related issues.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, such simplified classifications for NCCs in fuels may not be as germane, as both basic and nonbasic NCCs were shown to contribute to fuel degradation. 17,21,22 Additionally, the production of two fractions (i.e., basic and nonbasic) may not guarantee complete separation of different classes of NCCs within the same fraction when using GCxGC. For example, Adam et al 29 demonstrated that anilines and quinolines in the basic fraction coeluted in the GCxGC chromatogram, which complicated classification and quantitation of NCCs in diesel samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation